A Political Perspective on Business Elites and Institutional Embeddedness in the UK Code‐Issuing Process. (19th July 2013) - Haxhi, Ilir; van, Hans; Sorge, Arndt
Abstract Manuscript Type Perspective Research Question/Issue What is the role of institutional actors and business elites in the development of UK corporate governance codes? In the current paper, we explore the UK code‐issuing process by focusing on the UK actors, their power and interplay. Research Findings/Insights Our findings indicate, first, that the comply‐or‐explain principle, intertwined with the rich issuance of codes, reflects the diversity and permissiveness of British society and its ability to absorb contested corporate practices in a way that manages to preserve the status quo. Second, the UK business elites preserve their position in the corporate arena by using the principle of good governance, including the possibility to deviate from best practices, as an instrument of neutralizing institutional change. Third, the UK institutional and societal embeddedness gives carte blanche to elites to use corporate governance practices to serve their own interest. Theoretical/Academic Implications By emphasizing the strategic behavior of business elites embedded in the UK institutional configuration, we offer a political perspective on the national contextuality of the code‐issuing process. The worldwide diffusion of codes should not dissimulate their cross‐national contested nature. Codes reflect potential redistribution of power among institutional actors and business elites as well as the struggle over corporate resources between corporate actors (i.e., shareholders and managers) in maintaining their status quo. Practitioner/Policy Implications Practitioners should perceive codes as having different meanings depending on national contexts and national political constituencies. Codes reflect constellations of actors such as managers, shareholders, regulators and others, whose approach to codes and strategic interests are at least as important to know and understand as the verbatim content of codes.